2011
DOI: 10.1017/s1751731110002168
|View full text |Cite
|
Sign up to set email alerts
|

Breeding for robustness: the role of cortisol

Abstract: Robustness in farm animals was defined by Knap as 'the ability to combine a high production potential with resilience to stressors, allowing for unproblematic expression of a high production potential in a wide variety of environmental conditions'. The importance of robustness-related traits in breeding objectives is progressively increasing towards the production of animals with a high production level in a wide range of climatic conditions and production systems, together with a high level of animal welfare.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 80 publications
(86 reference statements)
0
66
0
4
Order By: Relevance
“…Several clinical studies have shown a relationship between CBG levels or CBG gene polymorphisms and metabolic parameters related to insulin resistance syndrome (e.g. Fernandez-Real et al, 2002;Barat et al, 2005;Richard et al, 2009), and the CBG locus has been shown to be linked with metabolic traits in several studies (see Moisan, 2010and Mormede et al, 2011aand 2011b for review), including in pigs (Desautes et al, 2002;Ousova et al, 2004), and we showed previously that CBG was a better predictor of carcass composition than cortisol levels (Ousova et al, 2004). In most cases, the physiological effects of CBG have been interpreted as resulting from the influence of CBG on the level and bioavailability of cortisol (Perogamvros et al, 2012;Moisan, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several clinical studies have shown a relationship between CBG levels or CBG gene polymorphisms and metabolic parameters related to insulin resistance syndrome (e.g. Fernandez-Real et al, 2002;Barat et al, 2005;Richard et al, 2009), and the CBG locus has been shown to be linked with metabolic traits in several studies (see Moisan, 2010and Mormede et al, 2011aand 2011b for review), including in pigs (Desautes et al, 2002;Ousova et al, 2004), and we showed previously that CBG was a better predictor of carcass composition than cortisol levels (Ousova et al, 2004). In most cases, the physiological effects of CBG have been interpreted as resulting from the influence of CBG on the level and bioavailability of cortisol (Perogamvros et al, 2012;Moisan, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A hyperactive or hyper-reactive hypothalamic-pituitary-adrenocortical (HPA) axis has an unfavorable effect on production traits such as growth rate and feed efficiency (Hennessy and Jackson, 1987) or body composition with an increased lipids/proteins ratio (Foury et al, 2005 and. A few studies established a positive relationship between HPA axis activity and robustness traits such as newborn survival, heat tolerance and resistance to diseases (see Mormede et al, 2011b and Mormede and † E-mail: Pierre.Mormede@toulouse.inra.fr a These data have been presented in a preliminary form at the 9th World Congress on Genetics Applied to Livestock Production, Leipzig (GE), 2010, paper 0169. Terenina, 2012, for review).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following question arises: what traits allow some individuals, populations or species to be more resilient to the synergistic effects of stress and infectious disease? Models have been developed in livestock for genetic selection and breeding for robustness based on the stress response (Mormède et al 2011) and, in the future, wildlife management too may employ similar strategies to build populations that are more resilient to the combined effects of stress and disease.…”
Section: (1) Climate Changementioning
confidence: 99%
“…The strategies used to produce animals that are able to overcome the perturbations in their physical environment and return to homoeostasis are dependent on the type of stress the animals face. On the one hand, Mormè de et al (2011) suggest that animals that produce a strong physiological response to acute stress adapt better to the stressor. The parallel cannot be made for behavioural responses where a phase of inhibition of all behavioural patterns is followed by a phase of activity.…”
Section: Genetics Of the Behavioural Response To Changes In The Physimentioning
confidence: 99%